Transistor com porta eletrolítica utilizando méis de abelhas nativas do Brasil como eletrólito - Fung, Maria Helena Lacerda de Oliveira (2022)
In this work, it was developed electrolyte-gated transistors using honey as electrolyte. The different honeys chosen to be applied are from native Brazilian stingless bees collected in the state of Paraná (south of Brazil). The use of honey as an electrolyte-layer in transistors has already been investigated in the literature, where it shows properties like: (i) a quick manipulation method for being used in-natura, maintaining its chemical characteristics such as viscosity, (ii) cheap, when compared to other commercial electrolytes, (iii) non-toxic and biodegradable, and also (iv) biocompatible, allowing it to be applied in biosensing, e.g. The developed transistors have interdigitated source and drain electrodes of tin indium oxide (ITO) and a channel composed of poly(3-hexylthiophene-2,5-dil) (P3HT), deposited by spin-coating process. The gate electrode is constituted by a platinum tip (Pt), which is partially immersed inside the honey drop that composes the transistor’s dielectric layer. Three different bees honeys were tested and studied in this work, being the honey from: Jataí (Tetragonisca angustula), Iraí (Nannotrigona testaceicornis) and Tubuna (Scaptotrigona bipunctata). The efficiency parameters extracted from the electrical characterization of the transistors were: the product of the field effect mobility with capacitance ( · ), threshold voltage (), transconductance () and the on–off ratio. Such parameters were compared to other recently published works related to electrolyte-gated transistors using honey from Apis Mellifera bees as electrolyte. The three tested honeys showed potential to be used in this class of transistors, and a certain set of parameters extracted from the electrical measurements have similarities among them. Finally, Honey-Gated Transistor were successfully obtained, operating in a voltage range of up to |2| , on-off ratio in the order of ∼ 101, and output current in the order of . We aim that that these transistors could be applied as a versatile and low cost platform in sensing and biosensing.